If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying dx + b = 2(x + -1d) Reorder the terms: b + dx = 2(x + -1d) Reorder the terms: b + dx = 2(-1d + x) b + dx = (-1d * 2 + x * 2) b + dx = (-2d + 2x) Solving b + dx = -2d + 2x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1dx' to each side of the equation. b + dx + -1dx = -2d + -1dx + 2x Combine like terms: dx + -1dx = 0 b + 0 = -2d + -1dx + 2x b = -2d + -1dx + 2x Simplifying b = -2d + -1dx + 2x
| 44b^2-208b-60= | | 9m+3m= | | 9k=3 | | 32r^5-60r^4-27r^3= | | 3x^3+x^2-8x+4=0 | | 7000d=63.5 | | 0.4v+2.4=-5.4v-3.4 | | 0.4a+2.4=-5.4v-3.4 | | 32s^5-76s^4-33s^3= | | -3+(5z+9)=(7z+5)-6 | | 12x^2-8xy-20y^2= | | -0.8z+3.3=0.9 | | -6-6+20x=5(4x-5)+13 | | -0.8a+3.3=9.9 | | -3x-10=-4 | | 3a=9a+24 | | 6g^2+13gc+6c^2= | | -2t-1=3t-16 | | 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 | | Y-2.8=2.2 | | Y-2.8=2.3 | | 15+8k=-34 | | 2x+3-x=6 | | 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 |